The application of fuzzy PID controller in coupled-tank liquid-level control system - Li Liang (2011 International Conference on Electronics, Communications and Control, 2011)
For the coupled-tank liquid-level control system with lumping lag and nonlinear characteristic, a fuzzy PID control approach is researched. In this approach, the characteristic of the control system is analyzed, the fuzzy PID controller is designed , a new implementation method of fuzzy control arithmetic is put forward. In kingview, the monitoring interface is designed, control program is carried out by new method, and the Liquid level control system is practiced. The result shows that this method is rationality and feasibility.